As competições sociais em grupos de Callithrix jacchus (Callitrichidae, Primates) são influenciadas pelo parentesco e pela convivência? - Lobato, Luzineide (2001)
The Callitrichidae family is characterized by flexibility in its mating system, being possible to find monogamous, polyandrid and polygynic groups. Its social organization and mating system can be defined by the interaction between ecological and demographic factors plus the degree of relatedness among the individuals in the population. The objective of this work was to demonstrate the influence of relatedness and coexistence on the establishment and maintenance of social relations between Callithrix jacchus adult males. Four pairs of related adult males (CP), 4 pairs with coexistence between the animals in the pair (CC) and 4 pairs with no relatedness (SP) were studied. The pairs in the group CC had been kept in the same cage for at least 8 months before the experiment and the pairs in the group SP were put together at the beginning of the study. Each animal was observed 3 times/week for 2 months, in 15 min. sessions, through focal time sampling with instantaneous record each minute. In the first month, only the pair of males was kept in the cage (Phase I) and in the second month, a female was introduced into the cage (Phase II). The affiliative, agonistic and sexual interactions were registered. Affiliative interactions showed similar frequencies for all groups in phases. There was also no significant difference in the agonistic interactions of the CP, CC and SP males in Pase I, even considering that group SP exhibited higher levels of agonism. In Phase II, there was a statistically significant increase comparing to the others. The results demonstrate that relatedness and coexistence are of great importance for maintaining reprodutive and social stability inside the group. Nonetheless, in this study, only one of the males in the pair had sexual interations with the females, except for 2 pairs. This was assured through mate guarding and agonism directed to the potencial competitor. The most probable mating system would be functional monogamy, where the males would present low levels of competition, if there is relatedness and coexistence among them; on the other hand, a strong competition if there is no relatedness between the individuals. Even so, a polyandric system would also have to be considered